2007
DOI: 10.1021/ol702901z
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Artificial Aldolase

Abstract: A new functional polymer where proline is bonded to polystyrene through a 1,2,3-triazole linker depicts characteristics targeted for an artificial aldolase. In spite of the hydrophobicity of the polymer backbone, the resin swells in water with building of an aqueous microenvironment. This property, arising from the formation of a hydrogen-bond network connecting the proline and 1,2,3-triazole fragments, is translated into a very high catalytic activity and enantioselectivity toward direct aldol reactions in wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
79
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(87 citation statements)
references
References 30 publications
6
79
0
Order By: Relevance
“…R. M. is grateful to the Spanish Ministerio de Ciencia e Innovación for a predoctoral fellowship. We also thank Dr. G. Gonzµlez and Dr. K. Gómez (ICIQ support unit) for their help with HRMAS 13 C NMR measurements and Dr. C. Rodríguez-Escrich for his assistance in the design and performance of the continuous flow system.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 3 more Smart Citations
“…R. M. is grateful to the Spanish Ministerio de Ciencia e Innovación for a predoctoral fellowship. We also thank Dr. G. Gonzµlez and Dr. K. Gómez (ICIQ support unit) for their help with HRMAS 13 C NMR measurements and Dr. C. Rodríguez-Escrich for his assistance in the design and performance of the continuous flow system.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…[11g] Taking into account the limitations associated to ligand anchoring through nucleophilic substitution, we have thoroughly investigated a new strategy for supporting catalysts onto Merrifieldtype resins through copper(I)-catalyzed Huisgen 1,3-dipolar cycloaddition (click chemistry) [12][13][14] and have shown that the resulting resins behave as highly active, enantioselective and diastereoselective, yet reusable, catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, in the transition state the organic non-polar reactants would be buried in the hydrophobic environment [18] whereas the entire system would be kept in water by a hydrophilic surface. After accomplishment of the reaction, the moderately polar aldol molecules would be squeezed out of the hydrophobic environment and locate themselves closer to the polar surface of the catalyst.…”
mentioning
confidence: 99%